EFEKTIVITAS MODEL PEMBELAJARAN MAKE A MATCH DALAM MENINGKATKAN KEMAMPUAN MENGENAL HURUF ABJAD PADA PADA ANAK TUNAGRAHITA RINGAN - Putri, Hidayatul; Damri, Damri (Universitas Muhammadiyah Ponorogo, 2024)
This study is based on the problems found in a child with mild mental retardation in class VII SLB Negeri 1 Lima Kaum, who still does not recognize all the letters of the alphabet. This study aims to prove whether the application of the Meka A Match learning model can improve the ability of mildly mentally retarded children to recognize alphabetic letters. This type of research is an experiment with a Single Subject Research (SSR) approach using the A-B-A design, and the subject is a mildly retarded girl in class VII SLB Negeri 1 Lima Kaum. Data collection techniques using action tests and visual graph data analysis in various conditions. The study lasted for 14 meetings, and the results showed that the Make A Match learning method was effective in improving the ability of mildly retarded children in recognizing alphabetic letters.